Analisis Kemampuan Representasi Matematis Ditinjau dari Self-Efficacy Siswa SMP Negeri 2 Pangkalan - Salsabila, Shalum Chanisa; Hakim, Dori Lukman (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2025)
Mathematics education is very important in life, students acquire mathematical skills and good mathematical attitudes, including mathematical representation ability and self-efficacy. The purpose of this study is to analyze how the level of students' mathematical representation ability in solving mathematics problems in terms of the level of mathematical self-efficacy of SMP Negeri 2 Pangkalan students. The method in this study uses descriptive qualitative method by explaining how students' mathematical representation ability is viewed from self-efficacy. Mathematical representation ability is explained as proposed by Bruner and self-efficacy is explained as proposed by Bandura. The test questions given consisted of 3 descriptive questions about flat space construction material. Out of 32 students, 6 students were selected again to be observed regarding self-efficacy. The results of the study obtained that the average value of the students' representation ability test results is 62.19 and is included in the moderate category. Students who completed the three stages of representation well were able to fulfill the three dimensions of self-efficacy. While students who did not complete the three stages of representation well, were not able to fulfill the three dimensions of self-efficacy.